(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Bilokonniy S. P. Using project method in environmental preparing future professionals preschooleducation. The article is devoted to the problem of professional-ekological training of specialists of preschooleducation. The method of projects to be one of the means of future teacher.